Association between parafunctional behaviors, clinical diagnoses, psychosocial factors and pain widespreadness in Finnish TMD pain patients in tertiary care - Iljin, Arvid; Assila, Ilona; Näpänkangas, Ritva; Teerijoki-Oksa, Tuija; Tolvanen, Mimmi; Sipilä, Kirsi (MRE Press, 2026)
Background: To evaluate the association of oral parafunctions with clinical DC/TMD (Diagnostic Criteria for Temporomandibular Disorders) Axis I diagnoses, Axis II biopsychosocial assessment and pain widespreadness in TMD pain patients in tertiary care.
Methods: 197 TMD pain patients were clinically examined and responded to DC/TMD OBC (Oral Behaviour Checklist) and Axis II comprehensive instruments. Patients were divided into Pain Drawing (PD) profile subgroups: PD-1 = head/face pain; PD-2 = head and neck/shoulder regional pain; PD-3 = widespread pain. Using the Graded Chronic Pain Scale 2.0 assessing pain-related intensity/interference, the patients were classified into TMD subtypes 1–3. Associations of frequent sleep bruxism (4–7 times per week) and daytime clenching (most/all of the time) with explanatory variables were evaluated with Independent Samples Kruskal-Wallis and chi-square tests and pairwise comparisons were made with Mann-Whitney U-test with Bonferroni correction.
Results: Frequent sleep bruxism was reported by 46.2% and daytime clenching by 67.5% of the participants. Sleep bruxism and daytime clenching associated significantly with muscle-related TMD diagnoses. Sleep bruxism and daytime clenching were significantly associated with anxiety (GAD-7, General Anxiety Disorder-7) subgroups, the highest prevalence being in the most severe subgroups. Frequent sleep bruxism was reported more by participants in TMD subtype 2 as well as those in PD-2 and PD-3 profile subgroups, with significant differences between PD-1 vs. PD-2 and between PD-1 vs. PD-3.
​​​​​​​Conclusions: Oral parafunctions are associated with muscle-related TMD diagnoses, anxiety symptoms and wider body pain, which should be considered in the assessment, treatment planning and personalized care of TMD pain patients.